The effect of silver sulfadiazine and zinc oxide creams on dose distribution during radiotherapy. Issue 2 (19th January 2015) - Fackrell, D.; Kirby, D.; Sanghera, P.; Hartley, A.
Abstract Introduction The use of metallic containing creams to prevent and treat radiodermatitis is controversial and lacking evidence base. We compare the dose effect of two metallic-based skin creams, which could be used for treating radiodermatitis, to a control. Methodology Universal containers of silver sulfadiazine cream, zinc oxide cream and aqueous cream were examined using a computed tomography scanner to assess their electron densities relative to water. Second, each cream was exposed to 100 kV and 6 MV photons. The relative doses were measured using an X-ray chamber. Results The relative electron density measured was similar for the silver sulfadiazine and aqueous creams. Zinc oxide was 40% higher. The relative dose measurements showed that silver sulfadiazine behaved in a similar way to aqueous cream; however, zinc oxide cream exhibited a dose difference of 11·0% in kV photons and −4·1% in MV photons. Conclusion Application of silver sulfadiazine appears unlikely to bring about significant changes in the dose distribution when compared with aqueous during MV or kV radiotherapy. While zinc oxide cream brought about more significant dose changes.